การเปรียบเทียบแรงยึดเฉือนและการรั่วซึมของวัสดุเคลือบหลุมและร่องฟันประเภทเรซินผสมฟลูออไรด์กับประเภทเรซินไม่ผสมฟลูออไรด์ - วรรณา โล้วพฤกษ์มณี (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
The purpose of this in vitro study was to compare the shear bond strength and microleakage between fluoridated (Helioseal F) and non-fluoridated (Helioseal) resin sealants. Fifteen human permanent molars were used to test the shear bond strength. The teeth were sectioned equally in buccolingual direction and randomly assigned to control (Helioseal) and experimental (Helioseal F) groups. After sealants were placed, the specimens were immersed in distilled water at 37℃ for 24 hours. Then, the shear bond strength was tested with the Instron Universal Testing Machine at a crosshead speed of 0.5 millimeter per minute. The mean and standard deviation of the shear bond strength of Helioseal F and Helioseal were 15.91±5.18 and 15.52±3.75 MPa. Paired T-test at 95 % confidence interval showed that the difference was not statistically significant. Thirty human upper permanent premolars were used to test microleakage. The teeth were randomly assigned to control and experimental groups of 15 each. Sealants were applied and specimens were immersed in distilled water at 37°c for 24 hours before subjected to thermocycling (5º-5 5 º C, 30 second dwell time, 500 times). They w ere applied with nail varnish and immersed in 1% methylene blue solution for 24 hours. Each tooth was sectioned at mesial and distal pits. The penetrating depth of dye in comparison to the sealant depth was measured with a grid by stereomicroscope at 40x magnification. The leakage was expressed as percentage of dye penetration to sealant depth. The mean and standard deviation of leakage of Helioseal F and Helioseal were 26.4 0±31.29 and 36.33±32.24 % of sealant depth. T-test at 95 % confidence interval showed that the difference was not statistically significant.